Comparative qualitative profile of various extracellular enzymes produced by two indigenous fungus Lentinus cladopus and Pleurotus pulmonarius - Rahi, Deepak K; Thakur, Shabnam; Malik, Deepika (International Journal of Scientific Research in Biological Sciences, 2018)
White rot fungi are well known prominent and efficient producers of various extra-cellular enzymes that play an essential role in various industries including food, paper, textile, medicine, etc. Therefore,the two important white rot species of Lentinuscladopus and Pleurotuspulmonarius were screened for the qualitative profile of various enzymes on solid medium. The result obtained revealed the remarkable presence of different extracellular enzymes including cellulase, mannanase, xylanase, pectinase, amylase, lipase and protease by both the fungi. However Pleurotuspulmonarius was found to be more efficient in producing almost each screened enzymes in comparision to Lentinuscladopus.